Ethnic discrimination in China's internet job board labor market - Margaret Maurer-Fazio (IZA Journal of Migration, 2012)
We conduct a large-scale field experiment to investigate how Chinese firms respond to Internet job board applications from ethnic minority and Han applicants. We signal ethnicity by using names that are typically Han Chinese and distinctively Mongolian, Tibetan, and Uighur. We find significant differences in callback rates by ethnicity. These differences vary systematically across ethnic groups. Not all firms discriminate-approximately half treat all candidates equally. State-owned firms are much less likely than others to discriminate in favor of Han candidates and both state- and foreign-owned firms are significantly more likely to treat candidates equally than do privately owned firms.
Keywords: J71; J23; J15; O52; P25; 330; Chinese firms; hiring; discrimination; ethnicity; Internet job boards; resume correspondence audit study